2014
DOI: 10.1093/mnras/stu481
|View full text |Cite
|
Sign up to set email alerts
|

Cross-correlations between soft and hard light curves depending on luminosity in the transient neutron star XTE J1701−462

Abstract: Using all the observations from Rossi X-ray Timing Explorer for the accreting neutron star XTE J1701-462, we carry out a systematic study on the cross-correlation function between its soft and hard light curves. During the entire outburst, XTE J1701-462 evolves from super-Eddington luminosities to quiescence, and shows both Z and atoll behaviours. Following the previous work, we divide the outburst into five intervals, one Cyg-like interval, three Sco-like intervals, and one atoll interval, according to their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Based on the systematic cross-correlation analysis of 4U 1608-52 (atoll source), Lei et al (2014) proposed that the distribution of the cross-correlations on the CCDs might be in evolution with the luminosity of the source. Similar results were also found in a Z-source XTE J1701-462 by Wang et al (2014). However, the evolution of cross-correlations along with the luminosity of the source and the spectral states has never been investigated in BHXBs, nor has the crosscorrelation analysis been performed on a whole outburst of BHXBs.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…Based on the systematic cross-correlation analysis of 4U 1608-52 (atoll source), Lei et al (2014) proposed that the distribution of the cross-correlations on the CCDs might be in evolution with the luminosity of the source. Similar results were also found in a Z-source XTE J1701-462 by Wang et al (2014). However, the evolution of cross-correlations along with the luminosity of the source and the spectral states has never been investigated in BHXBs, nor has the crosscorrelation analysis been performed on a whole outburst of BHXBs.…”
Section: Introductionsupporting
confidence: 73%
“…Tens of seconds to over 1500 seconds anti-correlated time lags were detected in the IMS of other BHXBs that are GRS 1915+105 (Choudhury et al 2005), XTE J1550-564, 4U 1630-47 (Sriram et al 2007), H1743-322 Raghurama Rao 2009) andGX 339-4 (Sriram, Rao, &Choi 2010). Similar kinds of anti-correlated time lags were observed in six other NS LMXBs, including four Z-sources (Cyg X-2 (Lei et al 2008), GX 5-1 (Sriram, Choi, & Rao 2012), XTE J1701-462 (Wang et al 2014) and GX 349+2 (Ding et al 2016)) and two atoll sources (4U 1735-44 (Lei et al 2013) and 4U 1608-52 ), and positive correlated time lags were also observed in them. Furthermore, the evolution of the crosscorrelation along the branches in the CCD or hardness intensity diagram (HID) was studied for the six NS LMXBs.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations